A150: Control of Cell Proliferation in Lupus Nephritis: The Role of miRNAs and HER2. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Costa Reis, Ana Patrícia; Russo, Pierre; Gallucci, Stefania; Sullivan, Kathleen E.
Abstract : Background/Purpose: miRNAS are responsible for post‐transcriptional gene silencing and typically regulate multiple targets. Our goal was to study the miRNA pattern of lupus nephritis (LN) in order to better understand its pathogenesis. Methods: A retrospective cohort study was performed on a large single‐center cohort of children exposed to anti‐Ro and/or anti‐La antibodies on whom prospective data has been collected since 1984. Inclusion criteria were: 1) first child born from a woman positive for anti‐Ro and/or anti‐La antibodies with a diagnosis of cutaneous lupus, systemic lupus erythematosus, Sjogren's syndrome, dermatomyositis or rheumatoid arthritis, 2) the mother underwent fetal echocardiography screening during pregnancy and/or the child had a postnatal ECG and 3) the child was ≥6 months old as of October 2013. We used Bayesian analysis for the association between prenatal use of AM and NLE. Results: A kidney LN miRNA signature was identified, which, according to Ingenuity pathway analysis, mainly reflected cell proliferation (p = 3.3E‐23‐0.049). miR‐26a, miR‐30b and miR‐4286 were significantly decreased in LN (p = 0.002; p = 0.005; p = 0.002). The levels of miR‐26a and miR‐30b were also decreased in the urine of LN patients when compared to controls (p = 0.03; p = 0.02). The genes significantly up‐regulated in the knockdowns of miR‐26a, miR‐30b and miR‐4286 when compared to controls were related to mitosis (p = 1.06E‐10). These results were validated by qRT‐PCR, including the increase on the expression of genes associated with cell cycle ( CCNE2, E2F8, MAD2L1, MYBL1 and POLQ ). Based on these results, we examined HER2 expression, a protein that regulates miR‐26a and miR‐30b levels in breast cancer cell lines. We found that it was highly increased in the glomeruli and tubular compartment of LN patients and not in other mesangioproliferative diseases. Moreover, the average of HER2+ cells in the glomeruli of NZM2410 mice was higher than in B6 or Balb/c mice (p < 0.0001; p = 0.009) and it was associated with proteinuria (p = 0.001). Finally, HER2 expression was increased in mesangial cells by α Ninterferon exposure (p = 0.02) and IRF‐1 transfection (p = 0.0009). Conclusion: The kidneys of LN patients have a miRNA pattern characterized by a significant decrease of miR‐26a, miR‐30b and miR‐4286, which is predicted to be associated with increased proliferation. In addition, miR‐26a and miR‐30b are also decreased in the urine of LN patients, which makes them interesting candidates as biomarkers. It was previously shown that trastuzumab, an antibody against HER2, produces therapeutic actions by up‐regulating miR‐26a and miR‐30b in breast cancer cell lines. Since we demonstrated that HER2 was highly increased in the kidneys of LN patients and NZM2410 mice, blocking HER2 may be a new promising pathway to decrease cell proliferation and damage in this disease.